Water intake in dairy goats – the effect of different types of roughages - Rebecca Ehrlenbruch; Margrete Eknæs; Trude Pollen; Inger Lise Andersen; Knut Egil Bøe (Italian Journal of Animal Science)
The aim of the current study was to investigate which type of roughage might influence the water intake in dairy goats. Eight goats were kept individually in single pens with one water bucket, with separated feeding table in order to register the drinking water intake, feed intake and milk yield for each goat. In experimental period 1 (3 days), four of the goats were fed hay and the remaining goats were fed silage, and vice versa in experimental period 2 (3 days). The goats drank more (P<0.0001) when they were eating hay compared to silage. Total water intake was higher (P<0.001) when they consumed silage than hay. The intake of silage was higher (P<0.0001) than for hay, but the opposite for dry matter intake. In conclusion, roughage type had an effect on water intake, with higher drinking water intake when fed hay than silage, but the opposite was true for total water intake.